Rehabilitate at home with the hospital +perto - Tiago Araújo; Elsa Rodrigues; André Novo; Joaquim Moreira; José Ribeiro Nunes (Associação Portuguesa dos Enfermeiros de Reabilitação, 2021)
Introduction: In line with the increase in the number of total knee replacement arthroplasties and the exponential use of new technologies by the general population, the development of a technological solution, by APP, which improves knowledge, as also increase literacy in health, enable adequate preoperative training and postoperative recovery.  Method: Framing of a digital rehabilitation program, under a communication channel of monitoring people who have undergone total knee arthroplasty from the preoperative period up to the first six weeks after surgery.  Expected results: An effective preoperative preparation and awareness of the real recovery, functionality and postoperative expectations, through recommendations, strategies and techniques, provided throughout the program. Track performance and feedback recovery as the application is used by participants through their responses to questionnaires and forms. The early identification of signs and symptoms, will allow the timely detection and monitoring of postoperative complications in order to reduce the rate of infections and readmissions.  Conclusion: Health care combined with technology, allows to reduce geographical barriers, bring health closer to the population and in this way prepare them for an advantageous transition in the health / disease process.